Reduksi Cod Dan Bod Air Limbah Domestik dengan Konsep Taman Constructed Wetland - Monik Kasman; Hadrah Hadrah; Fikri Firmanda (Universitas Batanghari Jambi, 2022)
Domestic wastewater is wastewater that comes from the activities of human daily life related to water use. If the wastewater can polute the receiving water such as river, if it is not treated before being discharged. This study aimed to determine the effectiveness and effect of the retention time of the garden with the concept of constructed wetland on the reduction of BOD and COD in domestic wastewater in terms of removal efficiency. The plants selected in this study were Kana plants and Kayu Apu plants, with a continuous circulation system. The variable retention time of wastewater in a garden reactor are 1, 2, 3, 4, 5, 6 and 7 days. The decrease in COD and BOD concentrations was analyzed by comparing COD and BOD before and after the study, as well as the effect of retention time on the effectiveness of COD and BOD reduction in gardens. The residence time did not significantly affect the decrease in the concentration of COD and BOD parameters, where as the highest percentage of COD and BOD reduction efficiency occurred on day 1 of 86% for COD and 84% for BOD.